The role of phytotoxic and antimicrobial compounds of Euphorbia gummifera in the cause and maintenance of the fairy circles of Namibia - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2019.